THE TRANSLATION OF INDONESIAN CULINARY TERMS INTO ENGLISH - Yora Yalu Sasongko; Yuli Widiana; Obat Mikael Depari (Humaniora Scientia, 2017)
This research focuses on translation, namely the techniques used to translateIndonesian culinary terms into English and its fidelity. Hence, it is descriptive innature. The library research is applied as the technique of data collecting.Moreover, translational equivalent method was applied as the technique of dataanalysis. The data of this research were all taken from the menu lists of tworestaurants - Desa Authentiek Indonesisch Restaurant (DAI) and RestoranKampoeng Aer (RKA). The analysis indicates that there were four techniquesapplied in the translation, namely, adaptation, description, literal translation, andborrowing. In addition, two combined techniques are also found in the data, theyare adaptation+description and borrowing+description. As a matter of fact, mostof the Indonesian culinary terms were translated using description technique.Meanwhile, the technique of borrowing was the least frequently appliedtechnique. Due to fidelity, 87 culinary terms were translated faithfully. It meansmost of the Indonesian culinary terms were translated with high level of fidelity.In this case, the terms were translated either by keeping the meaning and dynamicor by keeping the meaning only. Besides, there were 12 culinary terms translatedunfaithfully. Accordingly, only a little bit of the culinary term translations isclassified as those of low level of fidelity.